Manajemen Badan Usaha Milik Pesantren (BUMP) Maslakul Huda Kajen Pati - Dziyaul Lami’; Abu Hapsin (Iqtisad: Reconstruction of Justice and Welfare for Indonesia, 2019)
ABSTRACT The pesantren’s potential includes economic assets, religious teachings and ties between Kiai, santri, santri families, alumni, and the surrounding community to be important social capital in economic activities. This economic potential was realized by the Maslakul Huda Kajen Pati Islamic Boarding School, giving birth to several business units under the auspices of Islamic Boarding Schools. Then the pesantren business unit management is deemed necessary to be applied in order to create a pesantren sustainability. The study uses qualitative research method (qualitative research). The object of this study is BUMP Maslakul Huda with several business units, those are: BPRS Artha Mas Abadi, BPR Artha Huda Abadi, CV Mabadi Sejahtera and Agribusiness. The implementation of management functions at BUMP Maslakul Huda is planning, organizing, actuating and controlling, have gone well. With the implementation of management in BUMP and business units, what is produced is: the mechanism of the organization is running well, identifying problems and finding solutions and strategies to minimize failure and maximize the success of the program. Thus, the steps taken by BUMP and business units will encourage the economic independence of pesantren.